Amylin exacerbates tau pathology in the visual cortex of diabetic mice by impairing lysosomal activity - Daniel Moreira-Silva; Melike Yuksel; Moorthi Ponnusamy; Mitchell T. Hansen; Joseph D. McMillan; Sneha Geethakrishnan; Shuai Wang; Lisa A. Collier; Gopal Thinakaran (Genes and Diseases, 2025)
The aggregation of the peptide hormone amylin in the pancreas is a pathological hallmark of type-2 diabetes. Additionally, amylin can form aggregates in the brain, promoting β-amyloid deposition and tau phosphorylation in Alzheimer's disease. The cross-seeding between amylin and tau exacerbates tau pathology spread and synaptic loss, leading to neurodegeneration and cognitive deficits. Given the link between lysosomal dysfunction and tauopathy in the brain and amylin aggregation in the pancreas, we hypothesized that amylin could potentially worsen tau pathology in diabetic mice. We administered streptozotocin and/or amylin peripherally to the PS19 model of tauopathy at 3 months and characterized them at 6 months of age. We found that streptozotocin diminished body weight gain, increased blood glucose levels, worsened motor performance, and improved fear-conditioned memory in PS19 mice. Both amylin and streptozotocin administration prompted the emergence of tau pathology in the pancreas, which coincided with a decrease in the number of lysosomes in pancreatic islets. Mice treated with amylin and streptozotocin also developed robust tau pathology concomitant with lowering lysosomal cathepsin D levels in the visual cortex. These findings suggest that in diabetic mice, amylin administration diminished pancreatic lysosomes, possibly increasing the number of amylin aggregates that reached the brain and contributing to the worsening of tau pathology due to lysosomal impairment in the visual cortex. The outcome of our research enhances the understanding of the cellular pathways by which amylin may serve as a link between the pancreas-brain axis during diabetes, influencing the risk of developing tau pathology.